Impacts of Dryopteris serrato-dentata (Beddome) Hayata (Dhekishak) and Blumealacera DC. (Shialmutra) on rice and weed as growth inhibitor: an evaluation through the use of manure and fertilizer - Md. Tutul Hossen; Md. Liton Mia; Uttam Kumer Sarker; Ahmed Khairul Hasan; Md. Abdus Salam; Md. Shafiqul Islam (Discover Agriculture)
Abstract The present study was undertaken to know the suppression of weed growth through Dryopteris serrato-dentata (Beddome) Hayata (Dhekishak) and Blumea lacera Dc. (Shialmutra) residues and to estimate the manures and fertilizers effect with the Dhekishakand Shialmutra residues on boro rice at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, during the period from November 2022 to April 2023. There were two rice varieties viz., BRRI dhan29 (V1) and BRRI dhan89 (V2) having seven different treatments comprising of residues of Dryopteris serrato-dentata (Beddome) Hayata and Blumea lacera Dc., manures and fertilizers (t ha−1): Control (R1), Residues1.5 + Cowdung 5 (R2), Residues1.5 + Cowdung 2.5 + 50% of recommended dose Fertilizer (R3), Residues 1.5 + Vermicompost 5 (R4), Residues 1.5 + Vermicompost 2.5 + 50% of recommended dose Fertilizer (R5), Residues 1.5 + Trichocompost 10 (R6) and Residues 1.5 + Trichocompost 5 + 50% of recommended dose Fertilizer (R7) and was laid out in a randomized complete block design (RCBD) with three replications. Eleven weed species from seven families were found in this study. Minimum weed growth (1.68) was found in treatment V2R5 (BRRI dhan89 × Residues 1.5 + Vermicompost 2.5 + 50% of recommended dose Fertilizer) and the maximum was (67.40) in V2R1 (BRRI dhan89 × Control). The grain yield as well as the yielding parameters such as the effective tillers hill−1 (8.83), grains panicle−1 (124.98), grain yield (5.33 t ha−1), straw yield (6.49 t ha−1) were recorded highest in V2R5 (BRRI dhan89 × Residues 1.5 + Vermicompost 2.5 + 50% of recommended dose Fertilizer). It was obvious from the study that the residues had capability to suppress the weed growth and integrated manures and fertilizers enhances the yield performance of boro rice. Therefore, Dryopteris serrato-dentata (Beddome) Hayata and Blumea lacera Dc. residues combined with manures and fertilizers might be an efficient source of eco-friendly weed management and yield enhancement tool for sustainable boro rice production.